2020
DOI: 10.1097/md.0000000000022241
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits TNF-α induced HUVECs apoptosis and inflammation via downregulating NF-kB and AP-1 signaling pathway in vitro

Abstract: Background: Quercetin, a major flavonol, wildly exists in plantage, which has been reported to have an anti-apoptosis and anti-inflammation effects on vascular endothelial cells, but its underlying molecular mechanisms remain unclear. Objective: The aim of this study was to investigate the mechanisms of how quercetin inhibits tumor necrosis factor alpha (TNF-α) induced human umbilical vein endothelial cells (HUVECs) apoptosis and inflammation. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(90 citation statements)
references
References 41 publications
4
83
3
Order By: Relevance
“…It have been reported that TNF-α can directly induce apoptosis, while other inflammatory factors are reported less. However, in TNF-α induced HUVEC apoptosis, the concertation of TNF-αwas especially high (20 ng/mL to 200 ng/mL) 18 20 , while TNF-αconcertation in our studies was much lower (lower than 0.5 ng/mL) 21 . Thus, we speculated that inflammatory factors did not induced apoptosis, and they only played a role in promoting LPS-induced HUVEC apoptosis.…”
Section: Discussioncontrasting
confidence: 77%
“…It have been reported that TNF-α can directly induce apoptosis, while other inflammatory factors are reported less. However, in TNF-α induced HUVEC apoptosis, the concertation of TNF-αwas especially high (20 ng/mL to 200 ng/mL) 18 20 , while TNF-αconcertation in our studies was much lower (lower than 0.5 ng/mL) 21 . Thus, we speculated that inflammatory factors did not induced apoptosis, and they only played a role in promoting LPS-induced HUVEC apoptosis.…”
Section: Discussioncontrasting
confidence: 77%
“…The ACN fraction did not affect ICAM-1 and SELE expression ( Figure 4 B). In TNF-α-induced HUVECs, the upregulated VCAM-1, ICAM-1, and E-selectin were meaningfully reduced by pretreatment with quercetin [ 53 ]. ACNs and hydroxycinnamic acids present in blueberry and cranberry fruits reduced TNF-α-induced upregulation of various inflammatory mediators (IL-8, MCP-1, and ICAM-1) in HUVECs [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though in the present study no significant reduction in IL-1β and TNF-⍺ levels were associated with red wine consumption or polyphenols therapy, a propensity to a higher inhibition of these cytokines was observed in these two groups. However, numerous studies have confirmed that resveratrol and quercetin can suppresses the release of TNF-⍺ (Chen et al, 2020;Lee & Moon, 2005;Lee et al, 2019;Takada et al, 2004;Wang et al, 2020;Yuan et al, 2018). TNF-α is a proinflammatory cytokine, released by macrophages and has a vital role in periodontitis mediated bone loss by inducing the expression of mediators that amplify or sustain the inflammatory response such as the production of prostaglandins and matrix metalloproteinases (Algate et al, 2016).…”
Section: Discussionmentioning
confidence: 99%